Empowering Communities through Electoral Law Reform: The Challenge of Single-Candidate Elections in Indonesia - Julisa Sistyawan, Dwanda; Jayawibawa, Marcellus; Vallentino Neonbeni, Randy; Judijanto, Loso; Uticha Sally, Novian (Indonesian Journal of Legal Community Engagement, 2025)
This study examines the increasing prevalence of single-candidate elections in Indonesia’s regional (Pilkada) contests and their implications for community empowerment and local democracy. These elections undermine democratic principles by restricting voter choice, weakening political competition, fostering voter apathy, and disempowering communities. The study employs a community-based qualitative approach, focusing on the analysis of relevant laws, Constitutional Court decisions, reports from the General Election Commission (KPU), and scholarly literature. Findings indicate that the dominance of major party coalitions and entrenched incumbents marginalizes communities, limits alternative leadership, and weakens accountability. This study highlights that electoral reform is not merely technical but also a crucial instrument for empowering communities by restoring their sovereignty and agency in governance. To address these challenges, the study recommends comprehensive reforms, including strengthened political education for first-time voters, improved transparency, stricter controls on money politics, and greater opportunities for independent and minority candidates. Such measures are essential to revitalizing local democracy, promoting political diversity, and ensuring inclusive and competitive regional elections that reflect the aspirations and sovereignty of the people.